Systemic Racial in Stephen Adly Guirgis Play "Between Riverside and Crazy (2015) - Norazlin Norazlin; Muhd. Al- Havizh (English Language and Literature, 2022)
This article is about the analysis of a play Between Riverside and Crazy (2015) by Stephen Adly Guirgis. The problem of this analysis focuses on the issue of Systemic Racial. Systemic racial reflects the gap between White Amricans and African Americans. The aim of this analysis to find out the form of Systemic racial and to what extend do in fictional devices. The analysis deals with Joe R. Feagin’s concept of oppression. The result of this analysis shows that the discrimination and oppression happened to African Americans that cause by White Americans.